Recognize and Manage Stress With Positive Activities - Kholifah Kholifah; Agus Wardhono (Kontribusia : Research Dissemination for Community Development, 2022)
Life is a gift, so it must be fought for and always ready to face various challenges, in any situation and condition. The order of life is changing and the problems are getting more complex with the covid 19 outbreak. These problems bring tension or pressure, in general many people experience an imbalance, although there are still some who do not experience an imbalance. Parents, especially housewives, are very vulnerable to stress, this condition must not be allowed, it must be faced and managed, resolved in a way that is healthy and harmonious. The target of counseling is for the guardians of group B Muslim Kindergarten students at NU I Tuban. Submission of material is carried out by lecture and question and answer methods. The purpose of community service is to be able to recognize and be able to manage stress properly, healthy and harmonious and able to choose activities that are positive and useful. The results of the implementation of the extension went well and smoothly, the response was good, the indicators of the success of the counseling were many questions and even most of them tended to vent, and there were still many who misunderstood the meaning of stress and crazy.